Assessing the suitability of growth media in the glasshouse to standardize nematode resistance screening in banana (MUSA SPP.) - Mpanda, H.J.; Swennen, R.; Nakato, V.; Kisaakye, J.; Saikai, K.; Venkataramana, P.B.; Brown, A.; Coyne, D. (2025)
The burrowing nematode, Radopholus similis, is considered the most important nematode pest threatening banana production worldwide. Among the various nematode management strategies available, host resistance is one of the most promising. However, there is little information on host resistance in bananas against nematodes, including R. similis, which is partly explained by the inconsistency of the results and the resistance status of cultivars. To reduce such inconsistency, it would be beneficial to use a standardized detection protocol, utilizing appropriate planting substrates that allow the penetration and reproduction of nematodes without interfering with plant growth. Sterilized forest soil has commonly been used, but it limits the penetration of nematodes into the host roots due to its fine texture. Consequently, a more suitable substrate could improve the efficiency of screening for host resistance of bananas against nematodes. In this study, R. similis was used as a model nematode to evaluate cocopeat and river sand as alternative substrates to forest soil that is normally used in pot evaluations. In the pots, in vitro plants of the cultivars Yangambi Km5 and Grande Naine were planted, representing resistant and susceptible genotypes, respectively. The findings revealed that different substrates showed a differential impact on the growth parameters of the plants (underground biomass), allowing the penetration and reproduction of R. similis within the roots of banana plants. A high growth of plants in sterilized forest soil was observed, followed by cocopeat, and then river sand. In contrast, plants grown in river sand showed a higher number of R. similis in the roots and a greater reproduction rate, compared to those grown in cocopeat and sterilized forest soil. Although cocopeat favored plant growth, it hindered the penetration of R. similis and reduced reproduction rates. Moreover, there was a high proportion of root loss in the harvest due to the strong adherence of cocopeat to the roots. Therefore, it is suggested to use river sand as the most appropriate substrate to evaluate the response of banana genotypes to R. similis infection under greenhouse conditions. This would improve the efficiency of resistance evaluations of bananas against nematodes.